Sobre las interpretaciones de la oración “No hay un solo amigo en el mundo” - Ramírez Herrera, Víctor Gonzalo (2022)
This paper analyzes the sentence "no hay un solo amigo en el mundo" and explains two possible interpretations: in the first interpretation, there is no friend in the world and in the second, there is more than one. Our analysis is based on the syntactic behavior of the negative operator and suggests that, in one of the interpretations, the operator satisfies the so-called "Neg Criterion" generating negative concord, and, in the other interpretation, it does not. The final objective of this document is to present the descriptive and theoretical tools to approach this type of negation case from a syntactic perspective.